Study on dynamic modeling and transmission characteristics of inverted planetary roller screw mechanism - FENG Weidong; WANG Shisong; DENG Xingqiao; WU Guicheng; ZENG Liyuan; CAI Dajing (Jixie chuandong)
ObjectiveThe inverted planetary roller screw mechanism (IPRSM) is a new precision heavy-duty transmission device with high precision, large load, and long life. Due to the characteristics of multi-parts, multi-point contact, and multi-moving pairs, the dynamic behavior of the IPRSM are difficult to predict accurately.MethodsTo address this issue, a dynamic model of IPRSM was established by using the RecurDyn software, considering the complex contact and motion relation between the nut, the roller, the lead screw, and the cage. Based on verifying the validity of the dynamic model, the model was successfully used to analyze the influence of the nut speed and the screw load on the transmission characteristics of the IPRSM.ResultsThis research can provide theoretical support for the structural design and optimization of the IPRSM.